Graphene-based membranes for H2 separation : recent progress and future perspective - Chuah, Chong Yang (2021)
Hydrogen (H2) is an industrial gas that has showcased its importance in several well-known processes such as ammonia, methanol and steel productions, as well as in petrochemical industries. Besides, there is a growing interest in H2 production and purification owing to the global efforts to minimize the emission of greenhouse gases. Nevertheless, H2 which is produced synthetically is expected to contain other impurities and unreacted substituents (e.g., carbon dioxide, CO2; nitrogen, N2 and methane, CH4), such that subsequent purification steps are typically required for practical applications. In this context, membrane-based separation has attracted a vast amount of interest due to its desirable advantages over conventional separation processes, such as the ease of operation, low energy consumption and small plant footprint. Efforts have also been made for the development of high-performance membranes that can overcome the limitations of conventional polymer membranes. In particular, the studies on graphene-based membranes have been actively conducted most recently, showcasing outstanding H2-separation performances. This review focuses on the recent progress and potential challenges in graphene-based membranes for H2 purification.